2020
DOI: 10.1186/s12876-020-01253-8
|View full text |Cite
|
Sign up to set email alerts
|

Baseline levels of dynamic CD4+ T cell adhesion to MAdCAM-1 correlate with clinical response to vedolizumab treatment in ulcerative colitis: a cohort study

Abstract: Background: While the number of therapeutic options for treating inflammatory bowel diseases (IBD) is increasing, evidence for rational treatment decisions is scarce in many cases. In particular, appropriate biomarkers to predict the response to the anti-α4β7 integrin antibody vedolizumab are currently lacking. Methods:We performed a cohort study with 21 patients suffering from ulcerative colitis (UC), in which first-time treatment with vedolizumab was initiated. CD4 + T cells were isolated from the peripheral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
(39 reference statements)
1
11
0
Order By: Relevance
“…E.g., baseline microbial signatures were associated with the success of treatment [ 20 ], while transcriptomic signatures failed to predict outcomes [ 35 ]. Our group had observed that dynamic adhesion of peripheral blood CD4 + T cells to MAdCAM-1 in vitro and early changes in the expression of α4β1 integrin on circulating CD4 + T cells correlate with clinical response [ 21 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E.g., baseline microbial signatures were associated with the success of treatment [ 20 ], while transcriptomic signatures failed to predict outcomes [ 35 ]. Our group had observed that dynamic adhesion of peripheral blood CD4 + T cells to MAdCAM-1 in vitro and early changes in the expression of α4β1 integrin on circulating CD4 + T cells correlate with clinical response [ 21 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…While several potential biomarkers have been reported [19][20][21], such approaches require further validations before entering clinical practice. To the contrary, clinical characteristics of patients are easy to collect and may directly help to estimate outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In ustekinumab clinical trials, the most common adverse reactions included nasopharyngitis, upper respiratory tract infection, and cough (Davies et al, 2019). Some drugs target the components of the transport pathway, such as MadCAM-1 targeting the adhesion molecules, and anti-α4β7, natalizumab, vedolizumab, and etrolizumab targeting anti-integrin (Moens et al, 2019;Allner et al, 2020). At present, various studies have proved that vedolizumab has good safety in the treatment of IBD, but the high price increases the burden on the patients (Yu et al, 2018a).…”
Section: Therapeutic Targets and Drug-use Strategy For Inflammatory Bowel Diseasementioning
confidence: 99%
“…This suggested mechanistic explanation for non-response is supported by a recent study where it was shown that more T cells from responders than from non-responders adhered to MAdCAM-1 prior to initiation of vedolizumab therapy. 24 In contrast, a study by Paul et al reported higher sMAdCAM-1 values in non-responders than in responders. 25 Nevertheless, the results of this study cannot be compared to our study because the patient population (primarily CD patients vs all UC patients), dosing regimen (dosage optimization vs no optimization) and sampling time point (maintenance vs. induction) are considerably different.…”
Section: Serum Smadcam-1 Concentrations In Patients With Adequate Serum Vedolizumab Concentrationsmentioning
confidence: 86%